2017
DOI: 10.1111/cote.12322
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimicrobial and dyeing properties of walnut (Juglans regia L.) green husk extract for cosmetics

Abstract: Walnut green husk is one of the main waste products from walnut and could be used as a source of natural dyeing compounds such as juglone. The present study was conducted to evaluate the effective use of walnut green husk extract as a natural hair dye. Dyeing properties, fastness and antimicrobial behaviours of dyed hair and also a skin irritation test for natural hair dye on rat skin were examined. When the extract was mixed with ascorbic acid as a developer, ferrous sulphate as a mordant, and Aloe vera extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 35 publications
1
45
0
Order By: Relevance
“…33,34 However, a more detailed mechanistic study is required to substantiate this hypothesis. It is noted that applying excessive amounts of iron salts might pose a possible risk to consumers, 35 and therefore further work is required to determine the acceptable dosage of ferrous mordant in natural hair dyeing, or to find a safer alternative.…”
Section: Hair Dyeing Efficiency and Colour Fastnessmentioning
confidence: 99%
“…33,34 However, a more detailed mechanistic study is required to substantiate this hypothesis. It is noted that applying excessive amounts of iron salts might pose a possible risk to consumers, 35 and therefore further work is required to determine the acceptable dosage of ferrous mordant in natural hair dyeing, or to find a safer alternative.…”
Section: Hair Dyeing Efficiency and Colour Fastnessmentioning
confidence: 99%
“…However, hair dyeing is more complicated than that on textile fibers that can use long exposition times, high dyeing temperatures and toxic heavy metals (eg, alum). Among the few research papers dealing with dyeing hairs with plant colorants, only in a few cases the dyeing process was performed at physiologically acceptable temperature and pH . Several works reported that the fastness that is, affinity to hair fibers of many plant colorants can be improved by using appropriate mordants (eg, ferrous sulfate) and/or developers .…”
Section: Introductionmentioning
confidence: 99%
“…Among the few research papers dealing with dyeing hairs with plant colorants, only in a few cases the dyeing process was performed at physiologically acceptable temperature and pH . Several works reported that the fastness that is, affinity to hair fibers of many plant colorants can be improved by using appropriate mordants (eg, ferrous sulfate) and/or developers . However, these studies were limited to use wool, bleached black hairs or yak hairs as the dyeing substrates while in practice, especially in Asian countries, temporary or semi‐permanent plant hair dyes are more often applied on unbleached gray hairs for covering gray.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its simplicity, sensitivity and adaptability, the ELISA assay is the most commonly used method to detect aflatoxins (Biermann and Terplan 1980;Biermann and Terplan 1982;Danier et al 1994). To detect the aflatoxins, the direct competitive ELISA method is used.…”
Section: Resultsmentioning
confidence: 99%
“…Biologically active compounds from natural sources may provide health benefits as well as cosmetic benefits (dal Belo et al 2009). Today, botanical extracts can be found in everything from hand cream to lipstick (Frauen et al 2002;Gianeti et al 2013;Beiki et al 2018). Botanical extracts/oils may come in many forms (Marks 1997).…”
Section: Introductionmentioning
confidence: 99%